H2^+molecular hydrogen ion. Magnetic M1 transitions - Aznabayev Д.Т.; Bekbaev, A.K.; Korobov В.И. (Recent Contributions to Physics, 2024)
The magnetic dipole transitions in the homonuclear molecular ion H+2 are obtained for a range of u and L, vibrational and total orbital momentum quantum numbers, respectively. Calculations are performed in the nonrelativistic approximation. The effects of the ion spin structure on M1 transitions are also considered. Numerical calculations were carried out on the basis of “exponential” variational expansion. One of the simplest and most fully developed areas of application of quantum mechanics is the theory of atoms with one or two electrons. For hydrogen and hydrogen-like ions, calculations can be performed strictly in both Schrödinger’s non-relativistic wave mechanics and Dirac’s relativistic electron theory. The exact calculations are rigorous for an electron at a fixed Coulomb potential. Therefore, the hydrogen-like atom provides an excellent material for testing the validity of quantum mechanics. For such an atom, the correction terms that take into account the motion and structure of the atomic nucleus, as well as quantum electrodynamic effects, are small and can be calculated with great accuracy. Since the energy levels of hydrogen and hydrogen-like atoms can be experimentally studied with an amazing degree of accuracy, it turns out that it is possible to test the correctness of quantum electrodynamics to some extent accurately.